Clinical heterogeneity of polish patients with KAT6B–related disorder - Klaniewska Magdalena; Bolanowska‐Tyszko Anna; Latos‐Bielenska Anna; Jezela‐Stanek Aleksandra; Szczaluba Krzysztof; Krajewska‐Walasek Malgorzata; Ciara Elzbieta; Pelc Magdalena; Jurkiewicz Dorota; Stawinski Piotr; Zubkiewicz‐Kucharska Agnieszka; Rydzanicz Małgorzata; et al. (Molecular Genetics & Genomic Medicine, 2023)
Abstract Background Say‐Barber‐Biesecker‐Young‐Simpson (SBBYSS) variant of Ohdo syndrome is a rare, autosomal dominant and clinically heterogenous disorder, caused by pathogenic variants in the KAT6B gene located on chromosome 10q22.2. KAT6B encodes a highly conserved histone acetyltransferase belonging to the MYST family. Currently, diseases caused by pathogenic variants in KAT6B (KAT6B‐related disorders) comprise two allelic entities: SBBYSS variant of Ohdo syndrome and genitopatellar syndrome (GPS). Increase in the number of cases with overlapping GPS/SBBYSS phenotype which makes it necessary to redefine this group of phenotypes as KAT6B‐related disorders or KAT6B spectrum disorders. Individuals with SBBYSS usually present with facial abnormalities, hypotonia, joint laxity, feeding problems, and long thumbs/great toes. This syndrome also typically involves skeletal problems including patellar hypoplasia/agenesis. Methods Here we report six SBBYS syndrome patients with the same dysmorphic features but a different course of the disease. One known and five novel KATB6 pathogenic variants were identified by molecular diagnostics using Next Generation Sequencing (NGS). Results We present a detailed phenotypic analysis of six individuals with KAT6B‐related disorders, in whom a heterozygous pathogenic variant in KAT6B gene was found. In all of our patients facial dysmorphism as well as developmental and speech delay were present. Additionally, all but one patients presented with hypotonia, ocular abnormalities and long thumbs. Most of our probands showed blepharophimosis and skeletal (mainly knee) defects. Contrary to previously reported severe patellar defects (hypoplasia/agenesis) anomalies presented by our patients were less severe (dysplasia, habitual dislocation, subluxation) referring to KAT6B‐related disorders. Conclusion While most of the anomalies found in our patients comply with SBBYSS criteria, phenotypic differences in our probands support a broader spectrum of the disease phenotype. To establish the range of this spectrum, a detailed analysis of clinical variability among patients with SBBYSS requires further investigation.